A logic for the stepwise development of reactive systems - Madeira, Alexandre Leite Castro (2018)
D↓is a new dynamic logic combining regular modalities with the binder constructor typical of hybrid logic, which provides a smooth framework for the stepwise development of reactive systems. Actually, the logic is able to capture system properties at different levels of abstraction, from high-level safety and liveness requirements, to constructive specifications representing concrete processes. The paper discusses its semantics, given in terms of reachable transition systems with initial states, its expressive power and a proof system. The methodological framework is in debt to the landmark work of D.Sannella and A.Tarlecki, instantiating the generic concepts of constructor and abstractor implementations by standard operators on reactive components, e.g. relabelling and parallel composition, as constructors, and bisimulation for abstraction.